Kick Andy as an Inspirational Medium for Communicating Pancasila Values to Indonesian Youth (Oratio Directa, 2025)
This qualitative descriptive study examines Pancasila values in 30 Kick Andy episodes broadcast from 2019 to early 2025. Document review and qualitative content interpretation identify narrative themes, featured figures, and social issues associated with the five principles. Humanitarian concern and social justice are prominent in stories of disability, education, poverty, equality, tolerance, creativity, and community service; other principles appear through religious reflection, diversity, dialogue, and collective action. The representations show the program's potential as a nonformal educational medium connecting television storytelling with civic and character values. However, the source reports no coding book, coder reliability, audience interviews, surveys, or behavioral measures. The findings therefore establish content representation, not causal effects on youth character or value internalization. Audience research is needed to assess reception and longer-term outcomes among young viewers.
Keywords: Youth; Kick Andy; Inspirational media; Pancasila values; Character education